Catering incentives, sentiment investor, and dividend policy in six ASEAN countries - Shindy Dwita Nuansari; Eduardus Tandelilin; Bowo Setiyono; Eddy Junarsin (Cogent Business & Management, 2023)
Fundamentals alone are insufficient to explain why companies adopt a particular dividend policy. Dividend policy can also be seen from a behavioral perspective because companies serve investors who strongly prefer stocks that pay dividends, hereinafter referred to as dividend catering theory. This study employs a quantitative research design to investigate the theory of dividend catering in six ASEAN countries from 2012 to 2021. The research utilizes a dynamic panel regression approach with a Generalized Method of Moments (GMM) estimation system, drawing data from the Thomson Reuters database and The World Bank. This research produced several findings. First, we show essential differences in the dividend policies of companies across countries. Second, we find that low (high) sentiment tends to high (low) catering incentives, so companies decide to pay (not pay) dividends. Third, companies based in common-law countries exhibit a strengthened relationship between catering incentives and the likelihood of dividend payments. Our findings explain the factors that contribute to the increase and decrease of the catering dividend in the ASEAN region and contribute to the decision-making of a company's dividend payout by considering investor sentiment, which will ultimately increase firms' value.
Keywords: 650; ASEAN region; catering incentives; dividend policy; law system; sentiment investor